2010
DOI: 10.1111/j.1468-1331.2009.02844.x
|View full text |Cite
|
Sign up to set email alerts
|

A family with autosomal dominant leukodystrophy linked to 5q23.2–q23.3 without lamin B1 mutations

Abstract: This observation suggests that a mutation in an LMNB1 regulatory sequence underlies the variant ADLD phenotype. Thus, adult forms of ADLD linked to 5q23 appear to be more heterogeneous clinically and genetically than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 19 publications
3
44
1
1
Order By: Relevance
“…In one instance, the LMNB1 duplication event involved recombination between Alu sequences, but most of the duplication events appeared to involve short (Ͻ6-bp) regions of homology upstream and downstream of LMNB1 (75). Interestingly, one family with clinical features of ADLD manifested lamin B1 overexpression without a gene duplication event, presumably from a LMNB1 regulatory abnormality (76).…”
Section: Lamin B1 Gene Duplications and Autosomal Dominant Leukodystrmentioning
confidence: 99%
“…In one instance, the LMNB1 duplication event involved recombination between Alu sequences, but most of the duplication events appeared to involve short (Ͻ6-bp) regions of homology upstream and downstream of LMNB1 (75). Interestingly, one family with clinical features of ADLD manifested lamin B1 overexpression without a gene duplication event, presumably from a LMNB1 regulatory abnormality (76).…”
Section: Lamin B1 Gene Duplications and Autosomal Dominant Leukodystrmentioning
confidence: 99%
“…In addition, later, ADLD has been reported in other population or ethnic groups including Italian, French-Canadian, Japanese, Swedish, and French (Asahara et al, 1996; Marklund et al, 2006; Melberg et al, 2006; Meijer et al, 2008; Brussino et al, 2009, 2010). But the Japanese family reported by Asahara et al (1996) was only diagnosis by clinical manifestations and the pattern of inheritance, the family didn’t undergo gene detection.…”
Section: Discussionmentioning
confidence: 98%
“…It has been described that a large Italian family with clinical symptoms similar with ADLD and molecular analysis showed that the disease was segregated with the LMNB1 locus, and over expression of LMNB1 mRNA and LMNB1 protein has been identified among all the affected family members. But comprehensive genetic analysis found that no alteration or copy number variation for LMNB1 gene (Brussino et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations